2002
DOI: 10.1152/japplphysiol.00544.2002
|View full text |Cite
|
Sign up to set email alerts
|

Stent implantation alters coronary artery hemodynamics and wall shear stress during maximal vasodilation

Abstract: Coronary stents improve resting blood flow and flow reserve in the presence of stenoses, but the impact of these devices on fluid dynamics during profound vasodilation is largely unknown. We tested the hypothesis that stent implantation affects adenosine-induced alterations in coronary hemodynamics and wall shear stress in anesthetized dogs (n = 6) instrumented for measurement of left anterior descending coronary artery (LAD) blood flow, velocity, diameter, and radius of curvature. Indexes of fluid dynamics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 32 publications
2
41
0
Order By: Relevance
“…Implantation of instruments was described previously (24). Adult mongrel dogs of either sex and weighing between 18 and 24 kg were fasted overnight and anesthetized with barbital (200 mg/kg) and pentobarbital sodium (15 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Implantation of instruments was described previously (24). Adult mongrel dogs of either sex and weighing between 18 and 24 kg were fasted overnight and anesthetized with barbital (200 mg/kg) and pentobarbital sodium (15 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…Local blood flow velocity at the pericardial and myocardial luminal surfaces (Fig. 1B) of the LAD segment was determined using pulsed Doppler techniques (1,24,26). Briefly, a piezoelectric crystal with a stationary predetermined insonation angle that is fixed within a Doppler probe is deformed, emitting an ultrasonic pulse that propagates through the vessel wall to a specified depth.…”
Section: Methodsmentioning
confidence: 99%
“…The vessels were considered straight, noncompliant, and stationary, because studies have shown that myocardial motion has only a minor effect on flow distribution within the arterial tree relative to the effect of the blood pressure pulse, 34 and stent implantation causes straightening of the vessel and reduces its regional compliance. 35 In all considered cases, optimal stent deployment and complete apposition of stent struts against the vessel walls were considered, although in real-life inadequate stent deployment is frequent and multiple overlapping stents increase the likelihood of strut malapposition. 36,37 Thus, our model assumes perfect stent deployment that usually in clinical practice requires kissing-balloon after dilatation.…”
Section: Study Limitationsmentioning
confidence: 99%
“…A typical coronary inflow waveform (Fig. 4) (LaDisa et al, 2002) was then scaled to match the mean blood flow, and introduced as a time-varying Womersley velocity profile. Blood was assumed to be a Newtonian fluid with a viscosity and constant density of 4 cP and 1060 kg/m 3 , respectively.…”
Section: Cfd Simulationsmentioning
confidence: 99%
“…Implementation of these tools would better replicate relationships between local flow and global circulatory dynamics (Bove et al, 2007, Corsini et al, 2011and Kim et al, 2010. The rigid-wall assumption implemented here appears adequate when the aim of the study is the analysis of near-wall hemodynamic quantities (Chiastra et al, 2014) within the stent since implantation typically renders most of the artery rigid (LaDisa et al, 2002).…”
mentioning
confidence: 99%